The stn1-sz2 Mutant Provides New Insight into the Impacts of Telomeric Cdc13-Stn1-Ten1 Dysfunction on Cell Cycle Progression - Nathalie Grandin; Michel Charbonneau (Cells)
The conserved and essential Cdc13/CTC1-Stn1-Ten1 telomeric complex (CST) ensures chromosome stability by protecting telomere ends and regulating telomerase accessibility. In a recent study, we uncovered mutants of the S. cerevisiae CST, in which damage was sensed by the two major G2/M spindle checkpoints (one is Bub2-dependent and the other one Mad2-dependent), as well as the major G2/M DNA damage checkpoint (Mec1-dependent). In this study, we found, by fluorescence microscopy, that the stability of the mitotic tubulin spindle was profoundly affected in the best-studied of these mutants, stn1-sz2. Additional data from genetic analyses suggested the potential involvement of Stu1 and Stu2, as well as Slk19, in these defects. Throughout this study, we compared the phenotypes of stn1-sz2 with those of cdc13-1, the best-studied CST mutant, which also serves as a prototype of telomere-damage-characterized CST mutants. We propose that stn1-sz2 represents the prototype of cst mutants characterized by tubulin spindle damage. These newly described phenotypes potentially represent the basis for identifying new functions of the CST telomeric complex. These functions might consist of ensuring correct chromosome segregation through the stabilization of the mitotic spindle.